2010
DOI: 10.1051/m2an/2010019
|View full text |Cite
|
Sign up to set email alerts
|

Finite element discretization of Darcy's equations with pressure dependent porosity

Abstract: Abstract.We consider the flow of a viscous incompressible fluid through a rigid homogeneous porous medium. The permeability of the medium depends on the pressure, so that the model is nonlinear. We propose a finite element discretization of this problem and, in the case where the dependence on the pressure is bounded from above and below, we prove its convergence to the solution and propose an algorithm to solve the discrete system. In the case where the dependence on the pressure is exponential, we propose a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…They showed that the results they obtain are different from the solution to the classical Darcy's equation. Assuming that the "Drag coefficient" is a bounded function of the pressure in the generalized Darcy's equation, Girault et al [27] guaranteed the well-posedness of the system together with the convergence of a finite element method. When the dependence on the pressure is exponential (as in (1.2), the authors propose an interesting splitting algorithm, observed numerically to be robust in the parameter range tested.…”
Section: R a F Tmentioning
confidence: 99%
“…They showed that the results they obtain are different from the solution to the classical Darcy's equation. Assuming that the "Drag coefficient" is a bounded function of the pressure in the generalized Darcy's equation, Girault et al [27] guaranteed the well-posedness of the system together with the convergence of a finite element method. When the dependence on the pressure is exponential (as in (1.2), the authors propose an interesting splitting algorithm, observed numerically to be robust in the parameter range tested.…”
Section: R a F Tmentioning
confidence: 99%
“…A nonlinear Darcy fluid flow problem, with a permeability dependent upon the pressure was investigated by Azaïez, Ben Belgacem, Bernardi, and Chorfi [2], and Girault, Murat, and Salgado [11]. For a Lipschitz continuous permeability function, bounded above and bounded away from zero, existence of a solution (u, p) ∈ L 2 (Ω) × H 1 (Ω) was established.…”
Section: Introductionmentioning
confidence: 99%
“…In [2] the authors also investigated a spectral numerical approximation scheme for the nonlinear Darcy problem, assuming an axisymmetric domain Ω. A convergence analysis for the finite element discretization of that problem was given in [11].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in [6] the authors present optimal error estimates for a spectral discretization of this system which takes into account the axisymmetry of the domain and of the flow. On the other hand, in [33] the authors consider first the simplified model in which the exponential law defining the porosity is truncated above and below by positive constants, whose corresponding solvability and regularity analysis was previously developed in [6], and propose a primal finite element scheme with polynomial approximations of degrees k − 1 and k for velocity and pressure, respectively. Then, the case of a fully exponential porosity is analyzed in the second part of [33], where, under the heuristic assumption that the resulting model has at least one solution, a suitable change of variables involving only the pressure allows to split the problem into two consecutive linear systems, which are discretized by slight variants of the method from the first part.…”
Section: Introductionmentioning
confidence: 99%
“…Here we also consider the Darcy model with a fully exponential porosity from the second part of [33], assume again the heuristic hypothesis concerning the existence of solution, and apply the same change of variables employed there, but instead of a primal method, we opt for using the dual-mixed approach. As a consequence, the mixed boundary conditions arising from the transformation become readily employable and hence there is no need of additional regularity on the data nor of deriving any other boundary condition.…”
Section: Introductionmentioning
confidence: 99%